Исследование анизотропии диэлектрической проницаемости нематических жидких кристаллов в миллиметровой области длин волн - Кочержин, А. И.; Кухтин, М. П.; Черняков, Э. И. (My University, 2009)
The presented work accesses electrophysical properties of nematic liquid crystals based on cyanobiphenyl and azoxy LC under the frequency of 20-40 GHz with applied electric and magnetic static fields. The obtained results are interpreted in terms of molecular models. Possibilities of LC implementation into various electronic devises are also discussed in this thesis.
Keywords: анизотропия диэлектрической проницаемости; жидкий кристалл